Teachers' Strategies in Implementing Active Innovative Creative Efficient and Fun Learning in Islamic Religious Education Subjects in the Era of Globalization - Kurniati, Emi; Nadlif, Ainun (Al-Ulum: Jurnal Pendidikan Islam, 2025)
Technological developments have changed education, including Islamic Religious Education (PAI) learning. Learning Islamic Religious Education (PAI) is important for developing students' spiritual intelligence, morals and social skills, but many PAI teachers still have difficulty adapting learning strategies to the needs of the current generation. This research aims to explain the strategies teachers apply in implementing PAIKEM in subjects PAI in the era of globalization and identifying the challenges faced and formulating efforts to overcome them. This research uses descriptive qualitative methods to collect data through observation, interviews and documentation. The results show that the teacher's strategy focuses on creating an enjoyable learning environment with innovative methods and technology, as well as actively involving students. The challenges faced include differences in student abilities, low interest in PAI, and limited media. To overcome this challenge, collaboration between teachers and students is needed as well as innovation in learning methods. In this way, the quality of education can be improved, and students become more active and enthusiastic in learning.